CPC-063 How Do Pharmacists Document and Transmit Their Interventions? A Survey in Several French-Speaking Countries. (12th March 2013) - Kabiche, S; Fonzo-Christe, C; Prot-Labarthe, S; Guignard, B; Sigrist, T; Brion, F; Bourdon, O; Bonnabry, P
Abstract : Background: The role of a clinical pharmacist in providing and transmitting drug information to other health professionals varies greatly between countries. There is no consensus on the most efficient way to document and transmit interventions and its effect on the implementation of recommendations in practise. Purpose: To describe and then compare the methodology of pharmacist's interventions (PIs) in each of the following French-speaking countries: France, Switzerland, Belgium and Quebec. Materials and Methods: 527 on-line questionnaires were distributed (276 in France, 47 in Switzerland, 92 in Belgium, and 112 in Quebec). They contained 36 questions about clinical pharmacy work, the ways of transmitting information and its documentation in the patient record. Results: 160 hospitals answered (total 30.3%; France 33.7%, Switzerland 44.7%, Belgium 23.9%, Quebec 21.4%). In the Swiss hospitals, only 47.4% of pharmacists analysed pharmaceutical prescriptions while 97.4% did in France, 76.5% in Belgium and 100% in Quebec. The same trend could be seen while examining the pharmacist's presence on the wards: 42.1% in Switzerland, 58.4% in France, 85.7% in Belgium and 88.2% in Quebec. Communications channels for PIs also differed depending on countries: Swiss pharmacists mainly used the phone (56.7% of the cases), followed by personal visits (30.7%). In France and Quebec the preferred methods were writing notes in the patient's record in respectively 39.1% and 36.4% of the cases, followed by phone calls in 25.4% and 32.4%. In Belgium, the communication of PIs was most frequently done through personal visits (40%). Conclusions: Pharmacist's interventions in terms of ways of transmitting drug information and its documentation differ among the 4 countries. Differences in the pharmacist's integration into the ward teams, access to the patient record file and to the medical prescription probably explain the heterogeneity of our results. No conflict of interest.